6(4x-7)=3(8x+8)

Simple and best practice solution for 6(4x-7)=3(8x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4x-7)=3(8x+8) equation:


Simplifying
6(4x + -7) = 3(8x + 8)

Reorder the terms:
6(-7 + 4x) = 3(8x + 8)
(-7 * 6 + 4x * 6) = 3(8x + 8)
(-42 + 24x) = 3(8x + 8)

Reorder the terms:
-42 + 24x = 3(8 + 8x)
-42 + 24x = (8 * 3 + 8x * 3)
-42 + 24x = (24 + 24x)

Add '-24x' to each side of the equation.
-42 + 24x + -24x = 24 + 24x + -24x

Combine like terms: 24x + -24x = 0
-42 + 0 = 24 + 24x + -24x
-42 = 24 + 24x + -24x

Combine like terms: 24x + -24x = 0
-42 = 24 + 0
-42 = 24

Solving
-42 = 24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10n^2-4=506 | | 4+18r-2=9r+98-3r | | 159-4x=41x+14 | | 2x^3+5x^2-3x+5=0 | | 10-9x=23-16x | | x+(x-8)=60 | | 6y+4y=90 | | (8y-4y^2)+(3y-9y^2)= | | (0.5*x^2)-(1.5*x)=0.375 | | (0.5*x^2)-(1.5*x)-0.375=x | | q^2+2q=1 | | 2x^2-18x-8=0 | | 3x+30=10x-54 | | x^2-4.1x+2.2=0 | | (x^4)+(15x^2)-16=0 | | -7.5x=60.0 | | 3n-7=29 | | 0.7-10=0.5 | | 12t=-51 | | 9r=-36 | | x^2((x^2)+15)-16=0 | | -6(2b+3)+(13b-3)=0 | | 36c^2=4c | | 6x^2-16-20x=0 | | 36c^2=4v | | 2(3+6x)-4=50 | | 2.5q-1.2-2.1q=-0.6q-2.7 | | 6-3(3x-2)=-24 | | x+2=-35000 | | x^4+15x^2-16=-2 | | 3p+12=-2p | | 82-2x=34x+18 |

Equations solver categories